With concreteness details fade: dissociative effect of labelling of concrete and abstract stimuli on memory. Issue 2 (17th February 2022) - Hodel, Amy; Olszewska, Justyna; Falkowski, Andrzej
ABSTRACT: The current study sought to assess false memory formation in both immediate and delayed recognition for two different perceptually similar images: concrete images and abstract images. To test this, we adopted a modified version of the classical DRM task to study categorised pictures. Experiment 1 instructed participants to study sets of perceptually similar images, solve a math equation, and engage in a short-term memory (STM) recognition test. Following a delay, participants were given a long-term memory (LTM) recognition test. Experiments 2 and 3 were methodologically similar, however, excluded the distraction task allowing more time between encoding and retrieval (Experiment 2) and encouraged verbalisation of stimuli (Experiment 3). In three experiments, participants were more accurate in recognising images in STM than LTM and labelling images had a dissociative effect on LTM depending on the type of stimuli. Our results help identify the susceptibilities individuals experience while detecting changes in similar images.